Experiential Learning through Field Trips: An Overview - Rugaiyah Rugaiyah (STAI Hubbulwathan Duri, 2022)
The research aimed to describe teachers' and students' views in relation to the Field Trip Strategy on effect field trip in increasing students’ writing descriptive text. The respondents of this study were the students and English teachers of both government and private schools. The ideas and views of teachers and students were sought out regarding the benefits of educational field trips at jenior and senior schools level. To achieve the purpose of study two questionnaires were designed as research tools separately for teachers and students. One hundred and sixty respondents including 20 of English teachers and 140 students, were randomly selected. The questionnaire was used as a research instrument which was consisted of 25 items, collected data was analyzed by using the simple percentage method. The findings for each statement were made. Majority of the respondents had a view that educational Field Trip Strategy is helpful to explore their learning experience, The vast majority of respondents thought educational field trips helped students deal with advanced learning. According to a large majority of respondents' viewpoints, educational field trips help to provide a practical approach to the curriculum and help pupils acquire a greater interest in studying